Sarcocystis miescheriana infection in domestic pigs (Sus scrofa) in the Philippines - Claveria, Florencia G. (Animo Repository, 2001)
Sarcocystis miescheriana sarcocysts were identified in skeletal muscles of 9 (27%) of 33 swine slaughtered for human consumption. Sarcocysts were 144-180 μm × 20-38 μm in size. Ultrastructurally, the cyst wall resembled the type 10 sarcocyst wall. The villar protrusions (VP) were 3-4.5 μm long and 0.6-1.2 μm wide and had prominent longitudinally arranged microtubules extending from the VP tips to the granular layer (=ground substance). The parasitophorous vacuolar membrane with its underlying electron-dense layer (EDL) measured 25 nm in thickness. The base of the VP exhibited minute (0.42-0.87 μm) bulblike inpocketings. Each VP had 80-90 microtubules situated underneath the EDL. The granular layer was 0.5-1.2 μm thick, and contained hairlike microtubules continuous with those of the VP core. This is the first report of S. miescheriana in Philippine domestic pigs Sus scrofa.